Non-EU nationals in irregular employment in Ireland - Amy Stapleton; Emily Cunniffe; Emma Quinn (The Economic and Social Research Institute (ESRI), 2024)
Irregular employment, broadly understood as employment that is insufficiently covered by formal arrangements either in law or in practice, presents problems for the State in terms of tax revenue and regulation, whether it is undertaken by Irish, EU or non-EU nationals. For non-EU nationals, working in an irregular situation can create additional precarity, due to difficulties in exercising labour rights and accessing social security. This study discusses policy, law and data related to the irregular employment of non-EU nationals in Ireland, updating a 2017 EMN study on the topic. Reliable data on the extent of irregular employment of non-EU nationals are generally not available, in Ireland or internationally. However, information from employment inspections indicates that it occurs across a variety of sectors in Ireland, with food service activities the most prominent. Measures in place to prevent and identify the irregular employment of non-EU nationals in Ireland are presented, as well sanctions and outcomes for employers and employees.
Keywords: 330; Schwarzarbeit; Arbeitsmigranten; Arbeitsmarktpolitik; Arbeitsrecht; Irland